Feasibility of Artificial Insemination Network for Egyptian Buffalo Development: A Literature Reviews - Ibrahim Soliman; Ahmed F. Mashhour (Research Aspects in Agriculture and Veterinary Science Vol. 1, 2021)
Literature reviews confirmed that Egypt has a comparative advantage in milk production rather than red meat production, particularly from buffalo. Furthermore, water resources are becoming increasingly scarce, limiting horizontal expansion in fodder acreage. Furthermore, there is fierce competition between food and feed demand on available agricultural land resources. As a result, horizontal expansion in dairy buffalo stock would be impossible. As a result, the only option for buffalo development in Egypt is vertical expansion through increased milk yield to meet the current deficit in domestic milk production. The Egyptian consumer prefers buffalo milk for its color taste and high content of total solids, particularly fat. Buffalo milk is more expensive than cow milk, and its production is increasing faster than cow milk production. The proposed genetic improvement of buffalo milk yield is being accelerated using an artificial insemination (AI) network. A recent study [1], provided evidence that the return of genetic investment in dairy buffalo would be feasible, (IRR = 19.71%) However, according to official statistics, Egypt has only two AI-centers for buffalo selected buffalo sires, serving four AI-units. As a result, the goal of this study was to assess the feasibility of establishing an AI-network in Egypt by estimating (NPV, IRR, and payback period) and its sensitivity to unfavorable changes that the proposed program may face. The study used a field survey data collected from an AI-unit of the buffaloes’ semen and an AI-Center for raising buffalo sires in Nile Delta. The findings showed that, while the Egyptian economy’s average discount rate was 17.5 %, the estimated IRR for one AI-unit was around 35 % under the most likely scenario. A 10% decrease in semen price and a 10% increase in insemination costs would result in IRRs of approximately 28% and 31%, respectively. Under the most likely conditions, the estimated IRR for the AI-center was around 31%. 10% Decrease in Semen Price, and 10% increase in feed costs or in Sire’s price would result in 26%, 30% or 28% respectively. The lowest sale price of semen dose is thus the most effective variable on the IRR. Unfavorable changes, on the other hand, would keep investments with high incentives in establishing a feasible AI-Network for rapidly increasing the dairy buffalo milk yield.